168k views
3 votes
Use the graph that shows the solution to

f(x)=g(x) .

f(x)=−3/4x^2+3x+1

g(x)=2x

Use the graph that shows the solution to f(x)=g(x) . f(x)=−3/4x^2+3x+1 g(x)=2x-example-1
Use the graph that shows the solution to f(x)=g(x) . f(x)=−3/4x^2+3x+1 g(x)=2x-example-1
Use the graph that shows the solution to f(x)=g(x) . f(x)=−3/4x^2+3x+1 g(x)=2x-example-2
User Vinsce
by
5.4k points

1 Answer

7 votes

Answer:

The first graph will give the actual solution for f(x) = g(x).

Explanation:

The first function is
f(x) = - (3)/(4)x^(2) + 3x + 1 and
g(x) = 2^(x).

Now, f(0) = 1 and g(0) = 1

So, the point (0,1) is a solution for f(x) = g(x).

Again,
f(2) = - (3)/(4)(2)^(2) + 3(2) + 1 = 4 and
g(2) = 2^(2) = 4.

Hence, the point (2,4) is also a solution of f(x) = g(x).

Therefore, the first graph will give the actual solution for f(x) = g(x). (Answer)

User Wang
by
5.2k points